COMPARATIVE ACTIVITY OF TOTAL POLYPHENOLS AND ANTIOXIDANT COMPOUNDS FROM UNCARIA TOMENTOSA ENHANCED WITH CITRIC ACID - Roque Borda, Cesar Augusto [UNESP]; Aranda Medina, Camila Katerine; Silveira, Raiza Felismino [UNESP]; Mac-Lean, Priscilla Ayleen Bustos [UNESP]; de Souza, Angela Vacaro [UNESP]; Putti, Fernando Ferrari [UNESP]; Vicente, Eduardo Festozo [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2021)
Uncaria tomentosa, a climbing vine notable for containing high concentrations of oxindole alkaloids and phenolic compounds, is commonly used in traditional medicine as an anti-inflammatory and antioxidant agent. Also, the citric acid is a food additive widely used for conservation, due to its low cost. In this way, this study aims to evaluate the content of phenolic compounds from Uncaria tomentosa and investigate its antioxidant activity when citric acid, at different concentrations, is added to the extract. For this purpose, a gradient of citric acid concentrations was established, and the antioxidant profile from a aqueous extracts of the plant leaves and bark was analyzed by Folin-Ciocalteu essay; inhibition of the free radical of 2,2-diphenyl-1-picrylhydrazyl (DPPH); ferric reducing antioxidant power (FRAP), and scavenging capacity of cationic free radicals of 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). The results showed a synergistic effect between citric acid and antioxidant compounds from Uncaria tomentosa, presenting highly statistical significance, the synergistic effect was more efficient in the bark than in the leaves.
ACTIVIDAD COMPARATIVA DE POLIFENOLES TOTALES Y COMPUESTOS ANTIOXIDANTES DE UNCARIA TOMENTOSA POTENCIALIZADA CON ÁCIDO CÍTRICO
ATIVIDADE COMPARATIVA DE POLIFENÓIS TOTAIS E COMPOSTOS ANTIO-XIDANTES DA UNCARIA TOMENTOSA POTENCIADA COM ÁCIDO CÍTRICO
Keywords: ABTS; DPPH; Folin-Ciocalteu; FRAP; Synergistic Effect